Aliran dan pengaruh pemikiran akidah Lembaga Dakwah Islam Indonesia (LDII) di Provinsi Jambi : Analisis dari perspektif pemikiran Islam / Faizin - Faizin, Faizin (2017)
This research aims to study the School of thought and the Influence of Theological Thought of Lembaga Dakwah Islam Indonesia (LDII) in Jambi Provinsion: An Analysis from the Perspective of Islamic Thought. In order to provide a comprehensive accounts of The School of thought and Influences of Theological Thought of Lembaga Dakwah Islam Indonesia (LDII), the following variables are discussed: history and impetus for the establishment of Lembaga Dakwah Islam Indonesia (LDII), sources and theological foundation of LDII, and the impacts caused by the implementation of the theological thought in Jambi Provinsion. This research is qualitative in nature. Data were collected through observations, interviews, and documentations. To address the issue of validity this study used triangulation approach,i.e. by comparing views of different parties for checking and rechecking the data flow analysis was employed for data analysis. Results of this research show that the existence of Lembaga Dakwah Islam Indonesia (LDII) has undergone a long struggle and faced challenges from many elements of the community. From a theological perspective, the theology of Lembaga Dakwah Islam Indonesia (LDII) school of thought is not different from that of the Muslims in general. It uses Al-Qur’an and hadiths its references which supported by the logic and tends to be similar to salafi school of thought. The theological thought which has been preached and implemented has impacted on the members of LDII in many fields, i.e religion, politics, economy and socio-cultural aspects in general, and in Jambi Province in particular.